Active surveillance in patients with a PSA >10 ng/mL - Toren, Paul; Wong, Lih-Ming; Timilshina, Narhari; Alibhai, Shabbir; Trachtenberg, John; Fleshner, Neil; Finelli, Antonio (Canadian Urological Association Journal, 2014)
Introduction: The use of prostate-specific antigen (PSA) in active surveillance (AS) for prostate cancer is controversial. Some consider it an unreliable marker and others as sufficient evidence to exclude patients from AS. We analyzed our cohort of AS patients with a PSA over 10 ng/mL. Methods: We included patients who had clinical T1c–T2a Gleason ≤6 disease, and ≤3 positive cores with ≤50% core involvement at diagnostic biopsy and ≥2 total biopsies. Patients were divided into 3 groups: (1) those with baseline PSA >10 ng/mL, (2) those with a PSA rise >10 ng/mL during follow-up; and (3) those with a PSA <10 ng/mL throughout AS. Adverse histology was defined as biopsy parameters exceeding the entry criteria limits. We further compared this cohort to a concurrent institutional cohort with equal biopsy parameters treated with immediate radical prostatectomy. Results: Our cohort included 698 patients with a median follow-up of 46.2 months. In total, 82 patients had a baseline PSA >10 ng/mL and 157 had a PSA rise >10 ng/mL during surveillance. No difference in adverse histology incidence was detected between groups (p = 0.3). Patients with a PSA greater than 10 were older and had higher prostate volumes. Hazard ratios for groups with a PSA >10 were protective against adverse histology. Larger prostate volume and minimal core involvement appear as factors related to this successful selection of patients to be treated with AS. Conclusion: These results suggest that a strict cut-off PSA value for all AS patients is unwarranted and may result in overtreatment. Though lacking long-term data and validation, AS appears safe in select patients with a PSA >10 ng/mL and low volume Gleason 6 disease.